The Effect of Job Insecurity, Work Environment and Work Motivation on Turnover Intentions through Organizational Commitment of Employees - Wijayanti, Putri Dewi; Darmastuti , Ismi (Journal Research of Social Science, Economics, and Management, 2026)
Employee turnover is a critical challenge in industrial organizations, affecting productivity, operational costs, and organizational sustainability. High turnover can result from job insecurity, inadequate work environments, and low work motivation, all of which diminish employee satisfaction and organizational commitment. This study aims to examine the effects of job insecurity, work environment, and work motivation on turnover intention, with organizational commitment as an intervening variable. A quantitative research design was employed using structured questionnaires distributed to employees of PT. Besi Baja Makmur in Semarang, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.1. Validity and reliability of the instrument were ensured through factor analysis and Cronbach’s alpha testing, respectively. Purposive sampling was applied to select respondents representing diverse experiences in workplace conditions. The results indicate that job insecurity positively influences turnover intention, while a supportive work environment and strong work motivation reduce employees’ desire to leave. Organizational commitment mediates these relationships, strengthening retention effects. Employees with higher organizational commitment demonstrate lower turnover intention even when exposed to moderate job insecurity. The study concludes that improving workplace conditions, enhancing motivation, and fostering organizational commitment are essential strategies for reducing turnover. These findings provide actionable insights for human resource management in industrial organizations seeking to maintain a stable and productive workforce.